Baitut Tamwil Muhammadiyah: Role, application and impact of information technology - Yuniar Rakhman; Azhar Fahmi; Hendri Hermawan Adinugraha; Muh Hafidz Ma'shum (Fakultas Ekonomi dan Bisnis Islam, Institut Agama Islam Negeri (IAIN) Salatiga, 2022)
Information technology has a very important place in business in Islamic financial institutions, which supports all efforts from Islamic financial institutions to promote products, educate the public, support the progress of the financial system, and so on. This descriptive qualitative research was carried out at a sharia financial institution at BTM Pekalongan. This study aims to provide an overview of the information technology system implemented in the Pekalongan BTM environment. The instruments used in this study were observation and interviews. The results of this study indicate that the application of information technology has gone through a series of excellent analyzes, so the role of information technology is very large in the decision-making and development of BTM Pekalongan.